The Role of Islamic Law in Regulating Micro and Macro Finance: An Islamic Economic Perspective - Apriliani, Titin Putri; Nuryadin, Muhammad Birusman (Universitas Darussalam Gontor, 2024)
**English**This study explores the role of Islamic law in managing micro and macro finance, offering a comprehensive conceptual framework that integrates these two levels within the context of modern economic challenges. The research aims to demonstrate how principles of Islamic law, such as justice (‘adl), cooperation (ta’awun), and balance (tawazun), can create a sustainable and inclusive financial system. Using a qualitative approach with descriptive and normative analyses, this study reviews relevant literature and evaluates existing policies in countries implementing Islamic finance. The findings reveal that Islamic finance at the micro level, through mechanisms like Baitul Maal wat Tamwil (BMT), effectively empowers marginalized communities by providing ethical and interest-free financing. At the macro level, instruments such as sukuk and waqf are proven to enhance economic stability and foster sustainable development. The study also highlights the significant role of digital technology in expanding the reach and efficiency of Islamic finance. The results suggest that integrating Islamic finance principles at both micro and macro levels could address global economic disparities and create a stable economic ecosystem. Further research is recommended to explore technological innovations, such as artificial intelligence and big data, in enhancing Islamic financial systems. **Indonesia**Penelitian ini mengkaji peran hukum Islam dalam pengelolaan keuangan mikro dan makro dengan menawarkan kerangka konseptual komprehensif yang mengintegrasikan kedua tingkat tersebut dalam menghadapi tantangan ekonomi modern. Penelitian ini bertujuan untuk menunjukkan bagaimana prinsip hukum Islam, seperti keadilan (‘adl), kerja sama (ta’awun), dan keseimbangan (tawazun), dapat menciptakan sistem keuangan yang inklusif dan berkelanjutan. Dengan pendekatan kualitatif menggunakan analisis deskriptif dan normatif, penelitian ini mengulas literatur terkait dan mengevaluasi kebijakan di negara-negara yang menerapkan ekonomi syariah. Hasil penelitian menunjukkan bahwa keuangan syariah pada tingkat mikro, melalui mekanisme seperti Baitul Maal wat Tamwil (BMT), efektif memberdayakan masyarakat marginal dengan menyediakan pembiayaan etis dan bebas riba. Pada tingkat makro, instrumen seperti sukuk dan wakaf terbukti meningkatkan stabilitas ekonomi dan mendorong pembangunan berkelanjutan. Penelitian ini juga menyoroti peran penting teknologi digital dalam memperluas jangkauan dan efisiensi keuangan syariah. Hasil kajian ini menyarankan bahwa penerapan prinsip keuangan syariah secara terintegrasi pada tingkat mikro dan makro dapat mengatasi ketimpangan ekonomi global dan menciptakan ekosistem ekonomi yang stabil. Penelitian lanjutan diperlukan untuk mengeksplorasi inovasi teknologi, seperti kecerdasan buatan dan big data, dalam meningkatkan sistem keuangan syariah.